Looking to the horizon: the role of bilirubin in the development and prevention of age-related chronic diseases - Wagner, Karl-Heinz; Wallner, Marlies; Mölzer, Christine; Gazzin, Silvia; Bulmer, Andrew Cameron; Tiribelli, Claudio; Vitek, Libor (Clinical science (London, England, 2015)
Bilirubin, the principal tetrapyrrole, bile pigment and catabolite of haem, is an emerging biomarker of disease resistance, which may be related to several recently documented biological functions. Initially believed to be toxic in infants, the perception of bilirubin has undergone a transformation: it is now considered to be a molecule that may promote health in adults. Data from the last decade demonstrate that mildly elevated serum bilirubin levels are strongly associated with reduced prevalence of chronic diseases, particularly cardiovascular diseases (CVDs), as well as CVD-related mortality and risk factors. Recent data also link bilirubin to other chronic diseases, including cancer and Type 2 diabetes mellitus, and to all-cause mortality. Therefore, there is evidence to suggest that bilirubin is a biomarker for reduced chronic disease prevalence and a predictor of all-cause mortality, which is of important clinical significance. In the present review, detailed information on the association between bilirubin and all-cause mortality, as well as the pathological conditions of CVD, cancer, diabetes and neurodegenerative diseases, is provided. The mechanistic background concerning how bilirubin and its metabolism may influence disease prevention and its clinical relevance is also discussed. Given that the search for novel biomarkers of these diseases, as well as for novel therapeutic modalities, is a key research objective for the near future, bilirubin represents a promising candidate, meeting the criteria of a biomarker, and should be considered more carefully in clinical practice as a molecule that might provide insights into disease resistance. Clearly, however, greater molecular insight is warranted to support and strengthen the conclusion that bilirubin can prevent disease, with future research directions also proposed.
Keywords: kardiovaskulární nemoci; Humans; Chronic Disease; stárnutí; Bilirubin; lidé; Biomarkers; Aging; Diabetes Mellitus, Type 2; biologické markery; Cardiovascular Diseases; chronická nemoc; prognóza; bilirubin; Neoplasms; nádory; míra přežití; diabetes mellitus 2. typu; Prognosis; Survival Rate